Patterns of fetal lung growth in fetuses with isolated left-sided congenital diaphragmatic hernia. (2nd August 2016) - Antolin, Eugenia; Rodriguez, Roberto; Encinas, Jose Luis; Herrero, Beatriz; Muner, Marta; Perez, Ricardo; Ortiz, Luis; Bartha, Jose Luis
Abstract: Objective : To evaluate right lung growth pattern in fetuses with isolated left-sided congenital diaphragmatic hernia (iL-CDH) and to analyze the pattern according to postnatal outcome. Methods : Lung-to-head ratio (LHR) and observed-to-expected LHR (O/E LHR) were obtained in 58 cases. Correlation and regression analysis for the total number of measurements, general linear models for those cases with a least three serial measurements and linear mixed effect models were used to analyze the influence of gestational age on the right lung size. Cases expectantly managed and those with fetal endoscopic tracheal occlusion were analyzed separately. Results : LHR, but not O/E LHR, increased significantly with gestational age (GA) ( r =  0.43, p  = 0.003 and r =  −0.13, p  = 0.30, respectively). According to neonatal mortality, in those fetuses that died, LHR remained unchanged and O/E LHR decreased significantly with GA ( r =  0.07, p  = 0.65 and r =  −0.37, p  = 0.02, respectively). In those cases with at least three serial measurements, the same two patterns were found. Similarly, in cases with expectant management, surviving fetuses showed a significantly higher weekly increase in LHR ( p  = 0.01) and a trend to a lower weekly decrease in O/E LHR ( p =  0.17) than in those that died. Conclusions : Patterns of right lung growth in iL-CDH differ according to postnatal survival. Serial measurements, but not a single one, might increase the prediction of neonatal death.